Canoeing and kayaking - Turnbull, Stephanie (2016)
Learn about the equipment and skills you'll need to get started canoeing and kayaking.
Feel the thrill -- Know your boats -- Getting started -- Paddling -- Going under -- Wild water -- Smart thinking -- Fast and furious -- Endurance tests.
Includes bibliographical references and index.
Junior Library Guild
Ages 8-10.
Grades 3-5.
A Junior Library Guild selection (JLG)
Keywords: Boats and boating -- Juvenile literature; Canoes and canoeing -- Juvenile literature; Kayaks and kayaking -- Juvenile literature; Boats and boating; Canoes and canoeing; Kayaks and kayaking; Boats and boating; Canoes and canoeing; Kayaks and kayaking